2018
DOI: 10.1002/alr.22189
|View full text |Cite
|
Sign up to set email alerts
|

Highly multiplexed proteomic analysis reveals significant tissue and exosomal coagulation pathway derangement in chronic rhinosinusitis with nasal polyps

Abstract: Our proteomic analysis confirmed that the coagulation pathway is highly significantly deranged within nasal polyp tissue. The correlation between tissue- and mucus-derived exosomal fibrinolysis and coagulation protein alterations were strong, inverse, and highly significant. This lends further support to the emerging concept of exosomal proteomic analysis as a method to study chronic sinonasal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 44 publications
4
41
0
Order By: Relevance
“…Regulatory pathways for fibrinolysis and coagulation were significantly enriched in our subset of baseline‐increased proteins that decreased with steroids. This coincides with previous studies demonstrating alterations in coagulation‐pathway‒related proteins in CRSwNP . Specifically, nasal polyp tissue was characterized by excessive fibrin deposition in conjunction with reduced fibrin degradation from several pathways, including that of D‐dimer .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regulatory pathways for fibrinolysis and coagulation were significantly enriched in our subset of baseline‐increased proteins that decreased with steroids. This coincides with previous studies demonstrating alterations in coagulation‐pathway‒related proteins in CRSwNP . Specifically, nasal polyp tissue was characterized by excessive fibrin deposition in conjunction with reduced fibrin degradation from several pathways, including that of D‐dimer .…”
Section: Discussionsupporting
confidence: 91%
“…This coincides with previous studies demonstrating alterations in coagulation-pathway-related proteins in CRSwNP. 28,29 Specifically, nasal polyp tissue was characterized by excessive fibrin deposition in conjunction with reduced fibrin degradation from several pathways, including that of D-dimer. 28 Increased thrombin and Factor Xa locally can also increase the production of T-helper 2 cytokines and other inflammatory proteins 30 from nasal polyp fibroblasts, suggesting that the activated coagulation system may be involved in the formation and maintenance of nasal polyposis and associated eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…However, a greater number of target markers were poorly represented by swab sampling than by cytobrush (including TNF, IFNG, OSM, IL1A, and IL17C). Additionally, recent studies by Mueller et al 51,52 have also identified proteomic assessment of mucus exosome filtrates as a further promising noninvasive ("liquid biopsy") sampling option. Overall, the findings of this study indicate that these less invasive options acceptably reflect tissue patterns for several putative biomarkers of CRS and could thus be used in clinic and research settings as a proxy for tissue processes.…”
Section: Comparisons Of Sampling Methodologiesmentioning
confidence: 99%
“…Pilot studies by our group identified the development of a noninvasive, exosomal biosignature as a promising novel method for studying the etiopathology of CRSwNP while gaining more information about the diagnosis, prognosis, and treatment modalities of CRSwNP . Through this we identified that pappalysin‐A (gene name PAPP‐A) was significantly overexpressed in CRSwNP compared to controls.…”
mentioning
confidence: 99%